An Update on China’s Rural Land Tenure Reforms: Analysis and Recommendations Based on a Seventeen-Province Survey - Schwarzwalder, Brian; Riedinger, Jeffrey; Prosterman, Roy; Jianping, Ye (Columbia Journal of Asian Law, 2003)
The adoption of China’s revised Land Management Law in August 1998, combined with the issuance of the Decision of the Third Plenary Session of the 15th Central Committee “On Several Major Issues in Agriculture and Rural Work,” which called for implementation of “long-term, secure rural land use rights” and the drafting of additional legislation to protect those rights, marked the beginning of a new stage in China’s rural land tenure reforms. At that time, the Household Responsibility System (“HRS”) had already served as the foundation of Chinese agricultural and rural land policy for nearly twenty years, contributing to great advances in agricultural productivity and farmer economic welfare. This new stage of reforms reconfirmed collective ownership with contracting of use rights to farm households as the basis of China’s rural land tenure system while attempting to address some of the shortcomings identified in existing tenure arrangements throughout China. In contrast to the high degree of local variation and informality that had prevailed during the first two decades of HRS, the central government envisioned that, as part of the new round of reforms, all of China’s farmers would receive thirty-year land use rights embodied in written contracts and protected by national laws. In early 1999, the Central Rural Work Group announced the ambitious goal of full implementation of the new rights by the end of that year. An accurate assessment of the progress to date with respect to the goal of full implementation, and the impact of such progress on China’s farmers, can only be derived from systematic monitoring of the implementation process on a national basis. To that end, Renmin University and the Rural Development Institute (“RDI”) have cooperated on the design, conduct and analysis of two large-scale sample surveys, one in 19991 and a second in 2001, regarding the extent and nature of implementation of thirty-year rural land use rights. This paper discusses the findings of the second of these surveys, conducted with 1,617 rural households in seventeen Chinese provinces in July and August 2001. Analysis of the survey findings indicates that while as many as 85 million rural households may have benefited from the reforms, considerable work remains to achieve the goal of full implementation of long-term, secure land use rights.